Toughening static and dynamic damping characteristics of ultra-high performance concrete via interfacial modulation approaches. (February 2023) - Wei, Huinan; Liu, Tiejun; Zhou, Ao; Zou, Dujian; Li, Ye
Abstract: The damping capacity is one of major concerns for structures under dynamic loads, which significantly affects the safety and service life. Ultra-high performance concrete (UHPC) is a new generation of cementitious material characterized by superior mechanical strength and durability, exhibiting enormous potential in application to innovative structures. However, the weak steel fiber-matrix interface within UHPC leads to insufficient damping performance and poses threats to UHPC structures under extreme dynamic loading conditions. In this paper, various interfacial modulation approaches were investigated to improve static and dynamic damping properties of UHPC, including physical shape and chemical modification of steel fibers, macrofibers and microfibers hybridization. Results show that the interfacial modulation can significantly enhance damping ratio, loss factor and energy dissipation ratio of UHPC, where the chemical modification of steel fibers endows the highest damping ratio. The loss factor and energy dissipation ratio of UHPC reach 0.579 and 0.091 after interfacial modulation, which improved by more than 110% and 100%, respectively. The working mechanisms behind variations of damping performance are attributed to the toughening in interfacial bond and load transfer, leading to improvement in energy dissipating ability of interface. Furthermore, a comprehensive comparison between UHPC and existing vibration damping materials was conducted through multi-criteria analysis from the perspectives of damping performance, mechanical strength, processability and economic benefit, and UHPC with chemical modification of steel fibers exhibits the best overall performance. The findings contribute to inspiring a novel structural vibration control strategy through UHPC with enhanced static and dynamic damping properties for resisting extreme loads.